Numerical investigation of the influence of blade helicity on the performance characteristics of vertical axis tidal turbines. (September 2015) - Marsh, Philip; Ranmuthugala, Dev; Penesis, Irene; Thomas, Giles
Abstract: Previous research has shown that helical vertical axis turbines exhibit lower torque fluctuation levels than straight-bladed turbines; however little is known of the impact of blade helicity on turbine performance characteristics. To investigate these relationships the hydrodynamic characteristics of straight and helical-bladed vertical axis turbines were investigated using Three-Dimensional (3D) Computational Fluid Dynamics (CFD) models using a commercial Unsteady Reynolds Averaged Navier-Stokes (URANS) solver. Simulations of power output, torque oscillations, and mounting forces were performed for turbines with overlap angles from 0° to 120° and section inclination angles from −15° to 45°. Results indicated that straight-bladed turbines with 0° blade overlap generated the highest power output. Helical turbines were found to generate decreasing power outputs as blade overlap angle increased due to the resultant blade inclination to the inflow. Blade section inclination to the inflow was also found to influence power output. Some benefits of helical-bladed turbines over their straight-bladed counterparts were established; helical turbine torque oscillation levels and mounting forces were reduced when compared to straight-bladed turbines. For both straight and helical-bladed turbines maximum mounting force levels were found to exceed the average force levels by more than 40%, with large cyclical loading forces identified. Highlights: Straight bladed turbines generate more power than helical turbines for same frontal area. Helical turbines exhibit reductions in torque oscillation levels when compared to straight bladed turbine designs. Maximum mounting force levels exceeded the average force levels by more than 40% for both turbine designs.